Ungkapan Permohonan Dalam Bahasa Jepang - Windy Galuh Pramaswari; Ely Triasih Rahayu; Hartati Hartati (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2020)
This research is an analysis expressions of request in japanese language. The purpose of the research is to describe the variation of request expression and the underlying social factors. This type of research is descriptive qualitative in which the data are obtained from 3 Japanese dramas i.e From Five To Nine (5-9 Watashi ni Koi Shita Ikemen Sugiru Obousan), Shokojo Seira and Nigeru Wa Haji Da Ga. Data collection technique used observation and writing technique. Based on the result of analysis from 24 (twenty four) data, there are 5 (five) varian of request expression i.e te itakademasenka, te moraemasenka, te kudasai, te kure, and te. The underlying social factors are namely social discrepancy, social status, and formality.